Implementation of Multicultural Values in Islamic Religious Education Based Media Animation Pictures as Prevention of Religious Radicalism in Poso, Central Sulawesi, IndonesiaImplementation of Multicultural Values in Islamic Religious Education Based Media Animation Pictures as Prevention of Religious Radicalism in Poso, Central Sulawesi, Indonesia - Malla, Hamlan Andi Baso; Misnah, Misnah; Markarma, A. (International Journal of Criminology and Sociology, 2021)
This study aims to promote multicultural values in the culture of Sintuwu Maroso the Poso community through the transformation of education which is integrated with Islamic religious subjects based on animated image media as prevention of radicalism in the school and community environment. Research methods is a qualitative descriptive study in the form of writing and oral words from people who are the object of research, in conducting research, researchers as the main instrument whose role is to observe observations of documents and conduct interviews with informants, analyze data, interpret data and interpret data compiled a report on tracking the value of local wisdom on the multicultural value of Sintuwu Maroso in the Poso community. Islamic religious education learning that is integrated between Islamic religious material and cultural material of the Poso Sintuwu Maroso community can produce students who are always obedient to their God, behave well with others and are far from understanding religion and radical religious behavior in multicultural / change communities. student characters. Islamic religious education learning that is integrated between Islamic religious material and cultural material of the Poso Sintuwu Maroso community can produce students who are always obedient to their God, behave well with others and are far from understanding religion and radical religious behavior in multicultural / change communities. student characters